Nonequilibrium Electrons under Quantization Conditions - Ridley, B. K.; Zakhleniuk, N. A.; Bennett, C. R.; Constantinou, N. C.; Babiker, M. (physica status solidi (b), 1997)
An analytical kinetic theory is developed for a nonequilibrium electron gas under conditions when one or two degrees of freedom of the electron motion are quantized. We reveal universal features of the hot electron kinetics for an arbitrary quantizing potential. The theory can be applied to 2D or 1D electron gases or to 3D electrons subject to a quantizing magnetic field. It is shown that the kinetic behaviour of the quantized electrons is qualitatively different at low and high lattice temperature. We have obtained a set of new nonequilibrium distribution functions and presented novel non‐linear regimes of hot electron transport under relevant conditions.